Tandem Mass Spectrometry (LC-MS-MS): a Predominant Role in Bioassays for Pharmacokinetic Studies - Marzo, Antonio; Dal Bo, Lorenzo (Arzneimittelforschung, 2007)
Plasma concentrations of drugs and drug metabolites in bioavailability studies are routinely bioassayed with high performance liquid chromatography (HPLC), gas chromatography (GC), and liquid chromatography coupled with tandem mass spectrometry (LC-MS-MS) methods.In the 1980s and 1990s, HPLC had achieved a relevant role compared to GC and other techniques in pharmacokinetic bioassays. However, in the last few years the LC-MS-MS technique, known as tandem mass spectrometry, has attained a predominant role over all other techniques. This is because it requires a less amount of matrix, possesses better specificity and sensitivity, and requires a shorter operating time. In the experience of the authors, LC-MS-MS in fact requires on average 3-4 fold shorter time to complete a bioequivalence study when performed by one operator than does HPLC.The higher cost of the apparatus and technical assistance of LC-MS-MS are fully compensated by the shorter operating time. Part or most of the HPLC apparatuses have been or are being replaced by LC-MS-MS systems in laboratories operating in clinical and pre-clinical pharmacokinetics and, to a large extent, in those involved in assessing permeability in screening procedures of new chemical entities.This paper analyses the growing development of the LC-MS-MS technique and compares four couples of methods validated with HPLC or GC versus LC-MS-MS, giving analytical details of the two approaches.
Keywords: Gas chromatography; Liquid chromatography; Tandem mass spectrometry, bioassays, limit of quantification, plasma concentrations